Eco-friendly collapsible loess and preparation method thereof

By adding carboxymethylguar gum, activated coal gangue and magnetized water to the trapped loess, the problems of low strength and easy disintegration of soil in the trapped loess are solved by using volcanic ash reaction, ion exchange reaction and cementation, and the problems of low strength and easy disintegration of soil in the trapped loess are significantly improved, which significantly improves its shear strength, compressive strength and water stability.

CN119707361APending Publication Date: 2025-03-28ECONOMIC TECH RES INST OF STATE GRID HENAN ELECTRIC POWER +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411926351.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Due to poor particle grading, loose soil quality, large pores and weak cementing ability, wet loess lead to low soil strength and have poor engineering characteristics such as high compression, strong water sensitivity, and strong wet loess, which are prone to geological disasters and engineering problems.

Method used

Carboxymethylguar gum, activated coal gangue and magnetized water are used to improve the wet-deep loess. Through volcanic ash reaction, ion exchange reaction and cementation, the cohesion and cementation ability of the soil are improved, and the shear strength and compressive strength of the soil are enhanced.

Benefits of technology

It significantly improves the disintegration resistance and water stability of the wet loess, reduces the wet and disintegration properties, improves the mechanical properties of the soil, and avoids the occurrence of geological disasters and engineering problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707361A_ABST
    Figure CN119707361A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of civil engineering materials, and particularly relates to eco-friendly collapsible loess and a preparation method thereof. The eco-friendly collapsible loess is prepared from the following raw materials in percentage by weight: 0.8%-1.5% of carboxymethyl guar gum, 6%-10% of activated coal gangue, 70%-81.5% of collapsible loess and 10%-20% of magnetized water. According to the method, the shear strength and compressive strength of the collapsible loess are remarkably improved, the collapsibility and disintegration of the collapsible loess are greatly reduced, and the method is eco-friendly, turns waste into wealth and is low in preparation cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of civil engineering materials, and in particular relates to eco-friendly collapsible loess and a preparation method thereof. Background Art

[0002] As a special type of aeolian soil, collapsible loess is widely distributed in many countries, including Russia, the United States, and China. About 6.6% of China’s land area is covered by loess, and the total area of ​​collapsible loess is about 6.31×10 5 km 2 Due to the unique soil-forming environment, mineral composition and microstructure of collapsible loess, the collapsible loess has poor particle grading, loose soil, large pores, weak cementation ability, high soluble salt content and low soil strength. These disadvantages further lead to loess having poor engineering properties such as high compressibility, strong water sensitivity and strong collapsibility. These poor engineering properties have caused a series of geological disasters and engineering problems in actual engineering, such as landslides, foundation settlement, collapse, mud-rock flow, etc. Therefore, in actual engineering, various physical or chemical methods are usually used to improve and reinforce collapsible loess in order to eliminate its poor engineering properties.

[0003] At present, physical reinforcement for improving collapsible loess is mainly achieved by changing the internal structure of the soil and the particle size distribution of the soil. The most common methods include strong tamping, vibration compaction and replacement filling. However, the physical reinforcement process may cause noise pollution and even a series of vibration problems, which has certain disadvantages. The principle of chemical reinforcement is to add a certain reinforcement material to interact with the soil or react chemically to improve the cohesion and bonding ability of the soil, thereby achieving the purpose of improving the mechanical properties of the soil. Traditional reinforcement materials include lime, cement, fly ash, etc., but due to their disadvantages of polluting the environment and high carbon emissions, they have great limitations. In view of the defects of traditional reinforcement materials, it is of great significance to find eco-friendly loess reinforcement materials. Summary of the invention

[0004] In view of the shortcomings of the existing methods, the present invention provides an eco-friendly collapsible loess and a preparation method thereof.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] The invention discloses an eco-friendly collapsible loess, which is prepared from the following raw materials in percentage by weight: 0.8% to 1.5% of carboxymethyl guar gum, 6% to 10% of activated coal gangue, 70% to 81.5% of collapsible loess and 10% to 20% of magnetized water.

[0007] Preferably, the preparation method of the activated coal gangue is: soaking the coal gangue, drying it in the sun, preheating it at a low temperature, and then calcining it at a high temperature.

[0008] Preferably, the low-temperature preheating temperature is 60° C. to 80° C., and the time is 4 to 6 hours.

[0009] Preferably, the high temperature calcination temperature is 650-750° C. and the time is 3-5 hours.

[0010] Preferably, the molecular weight of the carboxymethyl guar gum is 2×10 6 ~3×10 6 D.

[0011] Preferably, the magnetized water is obtained by treating pure water in a magnetized water magnetizing device at a rate of 8 to 12 L / min for 3 to 5 hours.

[0012] An eco-friendly method for preparing collapsible loess comprises the following steps:

[0013] 1) crushing and drying the collapsible loess, and sieving to obtain fine-grained loess;

[0014] 2) Grinding the activated coal gangue, and fully mixing the activated coal gangue powder and fine-grained loess to obtain a mixed soil material;

[0015] 3) placing carboxymethyl guar gum in magnetized water to fully dissolve it to form a guar gum aqueous solution, and then introducing air into the guar gum aqueous solution to form a foam solution;

[0016] 4) Spray the foam solution evenly on the surface of the mixed soil material, seal it and let it stand, then mix it evenly, compact it, and cure it to form improved collapsible loess.

[0017] The positive beneficial effects of the present invention are:

[0018] 1. The physicochemical mechanism of improving collapsible loess by the present invention mainly includes: (1) volcanic ash reaction of activated coal gangue: the activated coal gangue undergoes volcanic ash reaction under alkaline conditions, thereby generating volcanic ash reaction products such as CaCO3, CAH (calcium aluminate hydrate), CSH (calcium silicate hydrate), and Gyp (gypsum). The generated volcanic ash reaction products fill the gaps between soil particles or adhere to the surface of soil particles, increase the friction and cohesion between soil particles, and can form gel particles with large specific surface area through agglomeration, which adsorb each other and thus improve the strength and stability of the soil; (2) ion exchange reaction: the Ca in the activated coal gangue 2+ 、Al 3+ High-valent cations and Na on the surface of soil particles +The exchange reaction takes place during the exchange. As the ion exchange reaction continues, the thickness of the double electric layer of the soil particles decreases, and the surface bound water film becomes thinner, thereby increasing the friction and cohesion between the soil particles. (3) Cementation: Carboxymethyl guar gum reacts with magnetized water to form a highly viscous guar gum hydrogel. These gelled products build "bridges" between non-adjacent soil particles, connecting them together and improving the integrity of the soil. In addition, carboxymethyl guar gum hydrogel aggregates individual soil particles into more compact aggregates through cementation, and forms a mutually penetrating biopolymer network structure with soil particles, thereby limiting the movement of soil particles, preventing the occurrence and further development of soil collapse, eliminating the collapsible characteristics of loess, and improving the anti-collapse and water stability of collapsible loess. (4) Magnetized water can make soil particles and improved materials disperse more evenly, reduce the optimal moisture content of collapsible loess, and improve the activity of activated coal gangue volcanic ash. It is also easy to make. The invention adopts magnetized water, carboxymethyl guar gum and activated coal gangue to improve the mechanical properties and collapsible properties of collapsible loess, significantly improves the shear strength and compressive strength of the collapsible loess, and greatly reduces the collapsibility and disintegration of the collapsible loess.

[0019] 2. Guar gum in the carboxymethyl guar gum of the present invention is a kind of biopolymer, which is a natural polymer produced by organisms such as plants and microorganisms, has the advantages of ecological environmental protection, rich variety and sustainable regeneration, and will not emit greenhouse gases in the process of improving collapsible loess, avoiding adverse effects on the environment. As time goes by, the guar gum in the soil will be degraded under the action of microorganisms, with sustainable regeneration, low carbon emission and eco-friendly advantages, and is a good renewable soil improvement material. Coal gangue is a solid waste generated in coal mining and processing, and the access is convenient and low in cost, which can greatly reduce the cost of preparing improved collapsible loess. The volcanic ash activity of the activated coal gangue is high at the same time. Using activated coal gangue as the improvement material of collapsible loess can not only reduce the occupation of arable land by coal gangue as solid waste, but also avoid the waste caused by the disposal of coal gangue waste. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a shear strength diagram obtained by direct shear test of the improved collapsible loess of the present invention;

[0021] Figure 2 A stress-strain curve obtained from the unconfined compressive strength test of the improved collapsible loess of the present invention;

[0022] Figure 3 A collapsible coefficient diagram obtained from a collapsible test of the improved collapsible loess of the present invention;

[0023] Figure 4This is a sample disintegration diagram obtained from the mud ball and fragment test of the improved collapsible loess of the present invention;

[0024] Figure 5 This is a microstructure diagram of the plain soil (unimproved loess) of the present invention;

[0025] Figure 6 This is a microstructure diagram of the improved collapsible loess according to the present invention. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with some specific embodiments.

[0027] The mineral compositions of the unimproved collapsible loess and activated coal gangue used in Examples 1 to 3 of the present invention and Comparative Examples 1 to 4 are shown in Table 1 below.

[0028] Table 1 Mineral composition of loess and activated coal gangue (wt%)

[0029]

[0030] Example 1

[0031] The invention discloses an eco-friendly collapsible loess, which is prepared from the following raw materials in percentage by weight: 1.25% of carboxymethyl guar gum, 6% of activated coal gangue, 77.75% of collapsible loess and 15% of magnetized water.

[0032] The above-mentioned eco-friendly collapsible loess preparation method comprises the following steps:

[0033] 1) Drying: crush and dry the collapsible loess at 60°C for 24 hours;

[0034] 2) Screening: Take the collapsible loess and screen it with a 2 mm sieve to obtain fine-grained loess;

[0035] 3) Water washing: Soak the gangue in water for one week. The gangue after water washing has been disintegrated and stabilized, and has less expansion. Then the soaked gangue is dehydrated by natural drying;

[0036] 4) Calcination: The dehydrated gangue is sent to a preheating furnace for low-temperature preheating at 70°C for 5 hours to remove moisture and some volatile substances, and then sent to a muffle furnace for high-temperature calcination at 700°C for 4 hours, with a loss on ignition of no more than 15%;

[0037] 5) Grinding: Put the activated coal gangue into a ball mill for mechanical grinding to obtain highly active coal gangue powder;

[0038] 6) Mixing: using a high-speed mixer, the highly active gangue powder obtained in step 5) and the fine-grained loess obtained in step 2) are fully mixed to ensure that the gangue powder can be evenly dispersed in the loess to obtain a mixed soil material;

[0039] 7) Modification: 100 g of guar gum was fully dissolved in 200 mL of isopropanol solution to obtain a guar gum suspension, and then 200 mL of a 10% NaOH aqueous solution was added, stirred evenly, heated to 85°C, and reacted for 1 h. Finally, 100 mL of a 25% sodium chloroacetate aqueous solution was added dropwise within 1 h, and the reaction was continued for 1 h. The material was cooled, washed, and dried. The molecular weight of the obtained carboxymethyl guar gum was 2×10 6 D;

[0040] 8) Magnetization: Put pure water into a magnetized water magnetizing device and process it at a rate of 9 L / min for 4 h to obtain magnetized water;

[0041] 9) Dissolving: Put carboxymethyl guar gum into magnetized water to fully dissolve it to form a guar gum aqueous solution, and then introduce air into the guar gum aqueous solution to form a foam solution;

[0042] 10) Stirring: Spray the foam solution from step 9) evenly on the surface of the mixed soil material from step 6), seal and let stand for 24 hours, and then stir evenly;

[0043] 11) Compaction: Compact and improve the collapsible loess according to the maximum dry density determined by the indoor compaction test;

[0044] 12) Curing: After compaction, place the soil in a standard curing box at a temperature of 20±2°C and a relative humidity of 95±3% for curing for not less than 28 days to obtain improved collapsible loess.

[0045] Example 2

[0046] This embodiment is basically the same as Example 1, and the similarities are not repeated. Some differences are: an eco-friendly collapsible loess is prepared from the following raw materials in weight percentage: 1.25% carboxymethyl guar gum, 8% activated coal gangue, 75.75% collapsible loess and 15% magnetized water.

[0047] Example 3

[0048] This embodiment is basically the same as Example 1, and the similarities are not repeated. Some differences are: an eco-friendly collapsible loess is prepared from the following raw materials in weight percentage: 1.25% carboxymethyl guar gum, 10% activated coal gangue, 73.75% collapsible loess and 15% magnetized water.

[0049] Comparative Example 1

[0050] This embodiment is basically the same as Embodiment 1, and the similarities are not repeated. Some differences are: the collapsible loess is prepared from the following raw materials in weight percentage: 1.25% carboxymethyl guar gum, 12% activated coal gangue, 71.75% collapsible loess and 15% magnetized water.

[0051] Comparative Example 2

[0052] This embodiment is basically the same as embodiment 1, and the similarities are not repeated. Some differences are: no coal gangue is added, and the components are mixed according to the mass ratio to include the following components: 1.25% carboxymethyl guar gum, 83.75% loess, and 15% magnetized water.

[0053] The above-mentioned eco-friendly collapsible loess preparation method comprises the following steps:

[0054] 1) Drying: crush and dry the collapsible loess at 60°C for 24 hours;

[0055] 2) Screening: Take the collapsible loess and screen it with a 2 mm sieve to obtain fine-grained loess;

[0056] 3) Modification: 100 g of guar gum was fully dissolved in 200 mL of isopropanol solution to obtain a guar gum suspension, and then 200 mL of 10 wt% NaOH aqueous solution was added, stirred evenly, heated to 85 ° C, and alkalized for 1 h. Finally, 100 mL of 25 wt% sodium chloroacetate aqueous solution was added dropwise within 1 h, and the reaction was continued for 1 h. The material was cooled, washed, and dried. The molecular weight of the obtained carboxymethyl guar gum was 2×10 6 D;

[0057] 4) Magnetization: Put pure water into a magnetized water magnetizing device and process it at a rate of 9 L / min for 4 h to obtain magnetized water;

[0058] 5) Dissolving: Put carboxymethyl guar gum into magnetized water to fully dissolve it to form a guar gum aqueous solution, and then introduce air into the guar gum aqueous solution to form a foam solution;

[0059] 6) Stirring: Spray the foam solution from step 5) evenly on the surface of the fine loess particles from step 2), seal and let stand for 24 hours, and then stir evenly;

[0060] 7) Compaction: Compact and improve the collapsible loess according to the maximum dry density determined by the indoor compaction test;

[0061] 8) Curing: After compaction, place the soil in a standard curing box at a temperature of 20±2°C and a relative humidity of 95±3% for curing for not less than 28 days to obtain improved collapsible loess.

[0062] Comparative Example 3

[0063] This embodiment is basically the same as embodiment 1, and the similarities are not repeated. Some differences are: guar gum is not added, and the components are mixed in the following proportions by mass: 6% activated coal gangue, 79% collapsible loess, and 15% magnetized water.

[0064] The above-mentioned eco-friendly collapsible loess preparation method comprises the following steps:

[0065] 1) Drying: crush and dry the collapsible loess at 60°C for 24 hours;

[0066] 2) Screening: Take the collapsible loess and screen it with a 2 mm sieve to obtain fine-grained loess;

[0067] 3) Water washing: Soak the gangue in water for one week. The gangue after water washing has been disintegrated and stabilized, and has less expansion. Then the soaked gangue is dehydrated by natural drying;

[0068] 4) Calcination: The dehydrated gangue is sent to a preheating furnace for low-temperature preheating at 70°C for 5 hours to remove moisture and some volatile substances, and then sent to a muffle furnace for high-temperature calcination at 700°C for 4 hours, with a loss on ignition of no more than 15%;

[0069] 5) Grinding: Put the activated coal gangue into a ball mill for mechanical grinding to obtain highly active coal gangue powder;

[0070] 6) Mixing: using a high-speed mixer, the highly active gangue powder obtained in step 5) and the fine-grained loess obtained in step 2) are fully mixed to ensure that the gangue powder can be evenly dispersed in the loess to obtain a mixed soil material;

[0071] 7) Stirring: Spray the magnetized water evenly on the surface of the mixed soil material in step 6), seal it and let it stand for 24 hours before mixing evenly;

[0072] 8) Compaction: Compact and improve the collapsible loess according to the maximum dry density determined by the indoor compaction test;

[0073] 9) Curing: After compaction, place the soil in a standard curing box at a temperature of 20±2°C and a relative humidity of 95±3% for curing for not less than 28 days to obtain improved collapsible loess.

[0074] Comparative Example 4

[0075] This embodiment uses unimproved collapsible loess.

[0076] The treatment steps of the above unimproved collapsible loess are:

[0077] 1) Drying: crush and dry the collapsible loess at 60°C for 24 hours;

[0078] 2) Screening: Take the collapsible loess and screen it with a 2 mm sieve to obtain fine-grained loess;

[0079] 3) Compaction: Compact the fine-grained loess according to the maximum dry density determined by the indoor compaction test;

[0080] 4) Curing: After compaction, place the soil in a standard curing box at a temperature of 20±2°C and a relative humidity of 95±3% for curing for not less than 28 days to obtain improved collapsible loess.

[0081] After the improved collapsible loess of Examples 1 to 3 and Comparative Examples 1 to 4 was treated, the mixed soil was compacted into cylindrical specimens of Φ39.1mm×80mm (diameter×height) and ring knife specimens of Φ61.8mm×20mm (diameter×height) by static compaction method. The cylindrical specimens were used for unconfined compressive strength test, and the ring knife specimens were used for direct shear test and collapsibility test. According to the requirements of each test, the compaction degree of the collapsible test specimen was 0.85, and the compaction degree of the remaining test specimens was 0.94. Three parallel specimens with the same mechanical properties were prepared in each group and sealed with plastic wrap. The prepared specimens were placed in a standard curing box with a temperature of 20±2°C and a relative humidity of 95±3% for curing. After curing for 28 days, the specimens were subjected to direct shear test, unconfined compressive test and collapsibility test.

[0082] The shear strength diagram obtained by the direct shear test in this embodiment is as follows: Figure 1 As shown. Figure 1 It can be seen that under the same vertical pressure conditions, the shear strength increases with the increase of curing age, and Example 2> Example 1> Example 3> Comparative Example 2> Comparative Example 1> Comparative Example 3> Comparative Example 4. Taking curing for 28 days as an example, under a vertical pressure of 100 kPa, the shear strengths of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are 180.08 kPa, 185.52 kPa, 177.93 kPa, 151.24 kPa, 168.87 kPa, 135.9 kPa and 117.24 kPa, respectively, which shows that the carboxymethyl guar gum and activated coal gangue combined with the present invention have the best shear strength effect on improving collapsible loess, and the improvement effect of carboxymethyl guar gum alone is better than that of activated coal gangue alone.

[0083] The stress-strain curve obtained from the unconfined compressive strength test of this embodiment is as follows: Figure 2 As shown. Figure 2It can be seen that with the addition of guar gum and coal gangue, the peak stress (i.e., unconfined compressive strength) in the stress-strain curve is significantly improved, and Example 2> Example 1> Example 3> Comparative Example 2> Comparative Example 1> Comparative Example 3> Comparative Example 4, the unconfined compressive strengths of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are 513.33 kPa, 526.75 kPa, 490.66 kPa, 453.33 kPa, 476.67 kPa, 371.73 kPa, and 330.89 kPa, respectively, wherein the unconfined compressive strength of Example 1 of the present invention is 513.33 kPa, which is 55.14% higher than the unconfined compressive strength of 330.89 kPa of Comparative Example 4, indicating that the unconfined compressive strength of collapsible loess improved by carboxymethyl guar gum and activated coal gangue combined with the present invention is good.

[0084] The collapsibility coefficient diagram obtained from the collapsibility test of the embodiment of the present invention is as follows: Figure 3 As shown. Figure 3 It can be seen that with the addition of guar gum and coal gangue, the collapsible coefficient of the improved collapsible loess is significantly reduced relative to that of the plain loess. For example, under a vertical pressure of 50 kPa, the collapsible coefficients of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are 0.0037, 0.0034, 0.0036, 0.0032, 0.0061, 0.0091 and 0.0254, respectively. By comparison, it is found that the effect of adding carboxymethyl guar gum and activated coal gangue to the collapsible loess for collapsible improvement is more significant than the effect of adding carboxymethyl guar gum or activated coal gangue alone. At the same time, with the continuous increase of the upper vertical pressure, the collapsible coefficient of the improved collapsible loess also decreases. When the upper pressure reaches 150 kPa or above, the collapsible coefficient of the improved collapsible loess is reduced to less than 0.015, that is, it is considered that it has completely lost its collapsible property. It can be seen that the addition of carboxymethyl guar gum and activated coal gangue has a positive effect on improving the collapsible properties of collapsible loess.

[0085] In addition, from the direct shear test, unconfined compression test and collapsibility test of the above-mentioned comparative example 1, it can be seen that as the amount of activated coal gangue added increases, although the collapsibility of loess is improved, the mechanical properties of loess are reduced, even lower than those of comparative example 2. This is because when the activated coal gangue is added too much, the activated coal gangue replaces the loess position, the loess content is reduced, the particles of the powder in the soil are reduced, the cementation and cementation of the coal gangue and loess are reduced, the friction between the soil particles is reduced, the cohesion effect is weakened, and the loess strength is reduced. Therefore, the preferred amount of activated coal gangue in the present invention is in the range of 6% to 10%.

[0086] The sample disintegration diagram obtained by the mud ball and fragment test in the embodiment of the present invention, the mud ball test sample adopts a spherical sample with a diameter of 1 cm, the fragment test sample adopts a cubic sample with a side length of 1 cm, and the compaction degree of the sample is 0.94. Figure 4 As shown. Figure 4 It can be seen that in the unmodified collapsible loess of Comparative Example 4, the disintegrated products of natural loess are loose fine particles and are easy to produce suspension, and the disintegration area is large. After the addition of coal gangue to improve Comparative Example 3, the disintegrated products of the improved collapsible loess become clear large particles or agglomerates that cannot form a suspension, and the disintegration area is relatively small. After the addition of guar gum to improve Comparative Example 2, the surface structure of the mud ball sample is intact, and no cracks appear, while the fragment sample partially falls off around, and the center part does not completely disintegrate. After the amount of activated coal gangue in Comparative Example 1 is too large, the improved collapsible loess sample has larger cracks, and partially falls off around, but does not completely disintegrate. After the addition of carboxymethyl guar gum and activated coal gangue to improve Example 1, Example 2 and Example 3, the sample surface remains intact, there are no obvious cracks, and basically no disintegration occurs.

[0087] The loess sample (compaction degree 0.94) was cut into small pieces and placed in a cold dryer for 6 hours. The middle part of the small piece was cut into a 4×4×2 mm slice, which was then fixed on a sample holder for gold spraying. The gold-sprayed sample was placed in a scanning electron microscope for observation. Figure 5 As shown in the figure, the natural loess is loose, has large pores, and has less cementing material between soil particles, which leads to the poor engineering properties of collapsible loess, such as high compressibility, strong water sensitivity, and strong collapsibility. In actual engineering, it is easy to cause a series of geological disasters and engineering problems such as landslides, foundation settlement, collapse, and mudslides. The microstructure of the improved collapsible loess in Example 1 of the present invention is as follows Figure 6 As shown in the figure, the addition of guar gum and coal gangue filled the pores between soil particles, effectively reduced the porosity of the soil, and made the soil sample more compact. At the same time, it was observed that an interpenetrating biopolymer network was formed between the soil particles and guar gum, which prompted the individual soil particles to agglomerate into denser aggregates, increased the cementing capacity of the soil particles, and improved the integrity of the soil.

[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.

Claims

1. An eco-friendly collapsible loess, characterized in that: The invention is prepared from the following raw materials in percentage by weight: 0.8% to 1.5% of carboxymethyl guar gum, 6% to 10% of activated coal gangue, 70% to 81.5% of collapsible loess and 10% to 20% of magnetized water.

2. The eco-friendly collapsible loess according to claim 1, characterized in that: The preparation method of the activated coal gangue comprises: soaking the coal gangue, drying it in the sun, preheating it at a low temperature, and then calcining it at a high temperature.

3. The eco-friendly collapsible loess according to claim 2, characterized in that: The low-temperature preheating temperature is 60° C. to 80° C., and the time is 4 to 6 hours.

4. The eco-friendly collapsible loess according to claim 3, characterized in that: The high temperature calcination temperature is 650-750° C. and the time is 3-5 hours.

5. The eco-friendly collapsible loess according to claim 1, characterized in that: The molecular weight of the carboxymethyl guar gum is 2×10 6 ~3×10 6 D.

6. The eco-friendly collapsible loess according to claim 1, characterized in that: The magnetized water is obtained by treating pure water in a magnetized water magnetizing device at a rate of 8 to 12 L / min for 3 to 5 hours.

7. A method for preparing the eco-friendly collapsible loess according to any one of claims 1 to 6, characterized in that: The steps include: 1) crushing and drying the collapsible loess, and sieving to obtain fine-grained loess; 2) Grinding the activated coal gangue, and fully mixing the activated coal gangue powder and fine-grained loess to obtain a mixed soil material; 3) placing carboxymethyl guar gum in magnetized water to fully dissolve it to form a guar gum aqueous solution, and then introducing air into the guar gum aqueous solution to form a foam solution; 4) Spray the foam solution evenly on the surface of the mixed soil material, seal it and let it stand, then mix it evenly, compact it, and cure it to form improved collapsible loess.